Nostalgic Collective Memory, Populist Rhetoric Exposure, and Social Transformation in Peri-Urban Communities of Palembang, South Sumatra, Indonesia: A Cross-Sectional Analytical Study - Firzan Dahlan; Grace Freya Purba (HM Publisher, 2026)
Nostalgic collective memory and exposure to populist rhetoric have emerged as significant sociocultural forces shaping contemporary social transformation in peri-urban areas of Southeast Asia. This cross-sectional analytical study examined the associations between nostalgic collective memory orientation, populist rhetoric exposure, and positive social transformation outcomes among 384 peri-urban residents in three purposively selected peri-urban sub-districts in a major city in South Sumatra, Indonesia. Participants were recruited through proportional stratified random sampling from sub-districts characterized by rapid urbanization and socioeconomic heterogeneity. They completed structured questionnaires assessing nostalgia levels (adapted 12-item scale, Cronbach alpha=0.82), populist rhetoric exposure (10-item scale), collective memory strength (8-item scale, alpha=0.78), community engagement, political trust, and perception of social transformation across six measured dimensions. Overall, 201 respondents (52.3%) perceived positive social transformation. Bivariate analysis demonstrated that high nostalgia levels were associated with 2.14-fold increased odds of perceiving positive social transformation (95% CI: 1.42-3.23; p=0.001), while high exposure to populist rhetoric was associated with 2.05-fold increased odds (95% CI: 1.36-3.09; p=0.001). Active community engagement was associated with 1.84-fold increased odds (95% CI: 1.22-2.77; p=0.004), and strong collective memory orientation was associated with 1.65-fold increased odds (95% CI: 1.10-2.48; p=0.016). Multiple logistic regression identified nostalgia level (AOR=1.89; 95% CI: 1.22-2.93; p=0.004), populist rhetoric exposure (AOR=1.76; 95% CI: 1.13-2.74; p=0.012), and community engagement (AOR=1.62; 95% CI: 1.05-2.50; p=0.029) as independent predictors. The model demonstrated moderate discriminative ability (AUC=0.735; Nagelkerke R²=0.187). These findings illuminate complex mechanisms through which nostalgic orientation, populist messaging, and community cohesion influence perceptions of social change in peri-urban Southeast Asian contexts.